Bacterial-mediated synthesis and characterization of copper oxide nanoparticles with antibacterial, antioxidant, and anticancer potentials - Talebian, Seyedehsaba; Shahnavaz, Bahar; Nejabat, Masoud; Abolhassani, Yasaman; Rassouli, Fatemeh B. (Frontiers in Bioengineering and Biotechnology, 2023)
The application of novel bacterial strains for effective biosynthesis of nanoparticles minimizes negative environmental impact and eliminates challenges of available approaches. In the present study, cell-free extract of Stenotrophomonas sp. BS95. was used for synthesis of copper oxide nanoparticles (CuONPs). Characterization of crude and calcined CuONPs was carried out by UV-vis spectroscopy, X-ray diffraction (XRD), fourier transform infrared (FTIR) spectroscopy, zeta potential, dynamic light scattering, field emission scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. Afterward, biogenic CuONPs were evaluated for antibacterial, antioxidant, and cytotoxic effects using broth micro-dilution method, DPPH assay and alamarBlue assay, respectively. Finally, molecular mechanisms behind anticancer effects of CuONPs was ascertained by real time PCR. UV-vis absorbance spectra registered surface plasmon resonance peaks at 286 nm and 420 nm for crude and calcined CuONPs, respectively. FTIR spectra exhibited bands associated with organic functional groups of bacterial proteins, confirming capping and functionalization of CuONPs. The average crystallite size of crude and calcined CuONPs was determined as 18.24 nm and 21.3 nm by XRD, respectively. The average zeta potentials of crude and calcined CuONPs were as-28.57 ± 5.13 mV and -29.47 ± 4.78 mV, respectively, indicating their high stability. Electron microscopy revealed that crude and calcined CuONPs were roughly spherical particles with an average size of 35.24 ± 4.64 nm and 43.68 ± 2.31 nm, respectively. Biogenic CuONPs induced antibacterial effects with minimal inhibitory concentrations ranging from 62.5 to 1000 μg/ml against Gram-negative and Gram-positive strains. The antioxidant activity of crude and calcined CuONPs was found to be 83 ± 2.64 % and 78 ± 1.73 %, respectively. More intriguingly, CuONPs exerted considerable cytotoxic effects on human colon and gastric adenocarcinoma cells, while induced low toxicity on normal cells. Anticancer effects of biogenic CuONPs were confirmed by significant changes induced in the expression of apoptosis-related genes, including P53, BAX, BCL2 and CCND1. Hence, biosynthesized CuONPs could be considered as potential antimicrobial, antioxidant and anticancer agents.